Blackboard use by faculty members in the Colleges of Applied Sciences in the Sultanate of Oman - AlNaibi, Salim Abdullah; Madarsha, Kamal Basha; Ismail, Nik Ahmad Hisham (International Educative Research Foundation and Publisher (IERFP), 2015)
This research was conducted to investigate the use of Blackboard by faculty members in the Colleges of Applied Sciences in the Sultanate of Oman and the factors affecting their use. A questionnaire was completed online by 257faculty members representing 43.05% of the total faculty population in these colleges. Results showed that Blackboard is still underutilized by faculty; it is mainly used as a depositary tool rather than for instructional and assessment purposes. Results also revealed that there are statistically significant differences in Blackboard use related to age, experience, specialization and college. However, other demographic variables (i.e. gender and academic rank) had no effect on Blackboard usage. Technology infrastructure and faculty support were identified as being the major factors leading to limited use of Blackboard in these colleges. It is recommended that immediate action be taken to address these issues; it is further recommended that additional research be undertaken to investigate student and faculty characteristics that relate to Blackboard usage